Reductions in sugar sales from soft drinks in the UK from 2015-2018 - Bandy, L; Scarborough, P; Harrington, R; Rayner, M; Jebb, S (BioMed Central, 2020)
Background: The consumption of free sugars in the UK is more than double the guideline intake for adults and close to triple for children, with soft drinks representing a significant proportion. The aim of this study was to assess how individual soft drink companies and consumers have responded to calls to reduce sugar consumption, including the soft drink industry levy (SDIL), between 2015 and 2018. Methods: This was an annual cross-sectional study using nutrient composition data of 7377 products collected online, paired with volume sales data for 195 brands offered by 57 companies. The main outcome measures were sales volume, sugar content and volume of sugars sold by company and category, expressed in total and per capita per day terms. Results: Between 2015 and 2018 the volume of sugars sold per capita per day from soft drinks declined by 30%, equivalent to a reduction of 4.6g per capita per day. The sales-weighted mean sugar content of soft drinks fell from 4.4g/100ml in 2015 to 2.9g/100ml in 2018. The total volume sales of soft drinks that are subject to the SDIL (i.e. contain more than 5g/100ml of sugar) fell by 50%, while volume sales of low and zero sugar (<5g/100ml) drinks rose by 40%. Conclusion: Action by the soft drinks industry to reduce sugar in products and change their product portfolios, coupled with changes in consumer purchasing, has led to a significant reduction in the total volume and per capita sales of sugars sold in soft drinks in the UK. The rate of change accelerated between 2017-2018, which also implies that the implementation of the SDIL acted as an extra incentive for companies to reformulate above and beyond what was already being done as part of voluntary commitments to reformulation, or changes in sales driven by consumer preferences.